Histopathology and Spatial Distribution of Putative Growth Factors in Relation to Bacterial Localization of Campylobacter jejuni Within the Ovine Gallbladder - Kreuder, Amanda J.; Lashley, Victoria; Yaeger, Michael; Schleining, Jennifer A.; Plummer, Paul J. (Frontiers in Veterinary Science, 2019)
Campylobacter jejuni is an important zoonotic pathogen that is the leading cause of both human foodborne bacterial gastroenteritis worldwide and ovine abortion in the United States. Previous studies have demonstrated that the gallbladder of ruminants is often positive on culture for Campylobacter sp., suggesting that this environment may serve as a chronic nidus of infection for maintenance of disease within populations. The objective of this study was to determine if previously identified putative growth promoting factors of C. jejuni are present within the gallbladder mucosa of sheep and to evaluate for bacterial co-localization of C. jejuni with these compounds following experimental inoculation. Direct gallbladder inoculation with C. jejuni sheep abortion (SA) clone clinical isolate IA3902 followed by immunohistochemical analysis and scanning electron microscopy allowed for identification of C. jejuni at the gallbladder mucosal surface and within the gallbladder submucosal glands. Histochemistry identified several putative Campylobacter growth promoting factors including neutral and acid mucins as well as L-fucose to be present both on the mucosal surface as well as in the gallbladder submucosal glands. In summary, following experimental inoculation of the ovine gallbladder, C. jejuni IA3902 was identified in direct contact with the gallbladder mucosal surface and deep mucosal glands in the same location as several putative growth promoting factors. This suggests the yet to be tested hypothesis that under natural conditions of infection, the gallbladder submucosal glands have the potential to provide a protected niche for chronic carriage of C. jejuni in animal hosts.